Upaya Guru Bimbingan dan Konseling dalam Meningkatkan Kedisiplinan Siswa di MAN 1 Padangsidimpuan - Latipa Hannum Harahap; Ali Daud Hasibuan (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Student discipline is one of the important factors to support the success of student learning and future plans for students in madrasas. BK teachers play an important role as an important actor to help students. This study aims to determine the efforts of counseling teachers at MAN 1 Padangsidimpuan in improving student discipline. The research approach used is qualitative research with a descriptive case study type of research. The research subjects were counseling teachers, homeroom teachers, subject teachers, and students of MAN 1 Padangsidimpuan who were taken by snowball sampling. Data collection techniques are carried out by observation, documentation, and interviews. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusions. The results showed that: The counseling teacher's efforts in disciplining students at Man 1 Padangsidimpuan are through preventive efforts, curative efforts, and development efforts. Preventive efforts can be made through; 1) provide clear, firm and thorough information about madrasa rules and regulations, 2) show attitudes and actions that students can emulate regarding discipline in madrasas; 3) provide motivation, study skills, and planning skills and self-direction to become outstanding students for each student; 4) create disciplinary ambassadors for students in madrasas. Curative efforts are carried out by counseling teachers through; individual counseling services, group counseling services, and case conferences. Then development efforts are carried out by the counseling teacher through efforts to increase learning motivation and student achievement motivation, planning for the future, and preparing agendas or daily activities. It can be concluded that the efforts made by the counseling teacher at MAN 1 Padangsidimpuan were effective in increasing student discipline. Keywords: effort, counseling teacher, student discipline, curative, preventive, development